The hybrid model for intention to adopt BYOD from the perspective of Pakistani doctors - Nisar, Saima (2021)
Mobile devices enable doctors to make informed decisions that provide quality healthcare outcomes. With Bring Your Own Device (BYOD), privacy and security are considered primary concerns to doctors since they handle sensitive and highly confidential data. To model a doctors’ intention to adopt BYOD using the Unified Theory of Acceptance and Use of Technology (UTAUT) alone does not seem adequate, particularly to address the security and privacy issues. Therefore, this study incorporates the UTAUT with two security and privacy factors from Protection Motivation Theory (PMT). The study aims to identify the determinant factors that affect the adoption of BYOD among Pakistani doctors. A theoretical study was conducted to identify the determinant factors, and then a hybrid model based on the identified factors was proposed. The hybrid model was developed by integrating the UTAUT model and PMT. Performance expectancy, effort expectancy, social influence and facilitating conditions from the UTAUT model were incorporated with perceived vulnerability, perceived severity, response cost and self-efficacy factors from PMT. Data collection was performed based on snowball sampling and was realised through an online survey instrument on Facebook. A total of 245 licensed doctors from Pakistan participated in the survey. The survey data were analysed using Structural Equation Modelling (SEM). The findings indicate that the hybrid model is an acceptable fit model as it explains 87 percent of the variance in behavioural intention. The results show that the UTAUT's performance expectancy, effort expectancy, facilitating conditions, and PMT's self-efficacy positively affected doctors' BYOD adoption, while PMT's perceived vulnerability and perceived severity had a negative impact. Theoretically, this study contributes to enhance the BYOD adoption model for the medical domain. The findings of this study also serve as a basis for hospital management to formulate and implement policies regarding data protection and security measures.